Epidemiological characterization of congenital syphilis in Teresina-Piauí in the period 2013 to 2017 (Research, Society and Development, 2021)
Congenital syphilis is a multiple system infection caused by Treponema pallidum, that it is transmitted to the fetus by the placenta any gestational period or during obstetric labor. In Brazil, there is an increase in the number of reports associated with syphilis during pregnancy and 80% with fetal contamination. The aim of the study was to analyze the epidemiological characteristics of Congenital Syphilis in Teresina-PI from 2013 to 2017. It is a quantitative research of descriptive nature with secondary data collected in DATASUS, through the Information System for Notification of Injuries (SINAN). The variables of the RNs / Children of the mother and the partner were included in the study, and only the maternal variables that were analyzed and not available by the System were excluded. For the organization of the data, we used Tabwin32, a data tabulator developed by DATASUS / MS. Descriptive statistics were used with absolute, relative frequencies to present the results. There were 1,180 cases of SC, and in 2013, 110 (9.32%) cases and 2015, 336 (25.82%). The main characteristics identified in the RNs / children were 591 (50.08%) male cases, 1,133 (96.01%) with ages ranging from 0 to 6 days, 755 (63.98%) brown, 1,003 85%) living in the urban area, and 1,052 (89.15%) with a diagnosis of recent SC. It was verified that 435 (36.86%) mothers had low schooling, 986 (83.55%) had prenatal care and 800 (67.79%) did not receive treatment. The high numbers of cases demonstrate fragility in prenatal care with low effectiveness of promotion and prevention actions, as well as treatment and determinants in the control of congenital syphilis.